O fechamento de escolas rurais do município de Limeira/SP: a negação do direito à educação aos trabalhadores do campo - Rinaldi, Fernando César (2022)
This research has aimed to analyze the problems that closing rural schools policy brings to individuals who live in rural areas. The work started from the hypothesis, verified and confirmed in the thesis, that the closure of the activities of these educational units causes social impacts to those affected by the procedure, as well as the subjects that may be impacted, due to a possible closure of the activities of the educational establishments public active in the field. The study was carried out in the city of Limeira, in São Paulo State, with students from the rural area enrolled in Kindergarten and Elementary countryside public schools in Limeira, and with those who had already been transferred to urban ones. For this, the research method historical-dialectical materialism was used, for the understanding of social reality; as well as bibliographic review techniques, documental and field research. The results show that, for the population already affected by the closure of the activities of the rural establishments where they studied, the most significant social impacts refer to the feeling of abandonment by the public power and the loss of the school as a reference for the community; for those who were not affected, the issue involving transportation, the distance to be traveled between home and school, and the parent´s concern for the safety of their child when studying in urban school are the impacts of greatest concern. It was noticed that, in view of the closure of rural schools, the population and workers living in the countryside must accept school transport or be denied the right to receive free education offered by the State, where they reside.